The Relationship between Salivary Beta-2 Microglobulin and Uremia Intensity in Men with Chronic Renal Failure - Marziyeh Ghasemi (Cell Journal, 2013)
Objective: This study defines the relationship between salivary beta-2 microglobulin (ß2-M) and intensity of uremia in male patients diagnosed with chronic renal failure (CRF).Materials and Methods: In total of 42 males were enrolled in a case-control study. There were 21 cases of CRF and 21 control cases. We collected 10cc of saliva plus 5 cc of blood from all patients to determine ß2-M, blood urea nitrogen (BUN) and creatinine (Cr) levels.Results: There was a correlation between the level of serum BUN and salivary urea in controls and patients, which was statistically significant for controls (p=0.028).The correlation between serum and salivary Cr was 0.195 in controls (p=0.398) and 0.598 in patients (p=0.006), which was statistically significant in patients. The correlation between serum and saliva was 0.133 (p=0.566) in controls and 0.078 (p=0.737) in patients, which was not statistically significant. The correlation between serum BUN and ß2-M was 0.168 (p=0.469) in the control group and 0.629 (p=0.002) in patients, which was statistically significant in patients. The correlation between serum Cr and ß2-M was 0.110 (p=0.635) in the control group and 0.678 (p=0.001) in patients, which was statistically significant in patients. The correlation between serum BUN and salivary ß2-M was 0.093 (p=0.0690) in controls and 0.152 (p=0.152) in patients, which was not statistically significant. The correlation between serum Cr and salivary ß2-M was 0.072 (p=0.070) in the control group and 0.286 (p=0.209) in patients, which was not statistically significant in either group.Conclusion: The results of the study indicated that salivary ß2-M cannot be used as a non-invasive indicator to detect the severity of renal failure.